Developing a framework for entrepreneurship ecosystem for developing countries: The application of institutional theory - Bylon Abeeku Bamfo; Felicity Asiedu-Appiah; Enya Ameza-Xemalordzo (Cogent Business & Management, 2023)
This is a qualitative study, which aims at developing a framework for entrepreneurship ecosystem for Ghana and other developing countries through the lens or with the application of institutional theory. In all, 61 owner managers were sampled for the study. In addition, 19 institutions were selected for the study. These were institutions that the researchers identified as having activities that were geared towards entrepreneurship capacity building and were willing to participate in the study. The sampling technique adopted was purposive, and the data collection methods were face-to-face interview with respondents and focus groups. The study revealed that there is a need for continuous building of the capacities of owner managers as a way of encouraging them to continuously push for innovative ideas that can be translated into acceptable products. The capacity-building responsibility is not the exclusive preserve of the government but all other institutions that have a stake in entrepreneurship development. However, governments of the developing world need to play a leading role in coordinating and regulating the activities of other stakeholders or institutions that operate at intertwined layers of regulative, normative, and cognitive pillars of an ecosystem.
Keywords: 650; capacity; development; ecosystem; entrepreneurship; institutions